Symbolic dimension of art and youth politics: analysis of an artistic intervention within the framework of a collective protest action - Bonvillani, Andrea (2021)
The aim of this article is to reflect on the political effect of art within a collective act of anti-repressive protest, spearheaded by young people in the city of Cordoba (Argentina). Focusing on the analysis of a specific artistic intervention and within the framework of a qualitative design, the data construction techniques implemented were: ongoing conversations, participatory observation, and in-depth interviews. It is concluded that art, currently one of the methods of youth politicization, makes it possible to go beyond the limits of meaning imposed by discursive rationality, opening up a multiplicity of senses associated with the sensorial-corporal and the imaginative. It is here that its political potential resides: the disruption of hegemonic times/spaces/senses makes possible a new distribution in the partition of the sensorial, the locus of politics in Rancierian terms.